2021
DOI: 10.1111/ijn.12948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daily sedation interruption in intensive care unit patients undergoing mechanical ventilation: A meta‐analysis of randomized controlled trials

Abstract: Aim: This study aimed to assess the effects of daily sedation interruption on the mechanical ventilation duration and relevant outcomes in mechanically ventilated patients in the intensive care unit (ICU).Background: Previously, three meta-analyses on the association of daily sedation interruption with the mechanical ventilation duration have reported conflicting findings, and these did not support current guideline recommendations that daily sedation interruption can be routinely used in mechanically ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…1 , 30 Furthermore, a variety of approaches to overcome barriers have been suggested. 31 For example, optimal use of analgesia and sedation, 32 close monitoring of delirium, 33 interrupted sedation, 34 and a combination of these 23 would be helpful to overcome barriers related to consciousness, which are high among patients with MV. Mobilization practices should be optimized according to situations and barriers, irrespective of COVID-19 infection, the kind of disease, and its severity.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 30 Furthermore, a variety of approaches to overcome barriers have been suggested. 31 For example, optimal use of analgesia and sedation, 32 close monitoring of delirium, 33 interrupted sedation, 34 and a combination of these 23 would be helpful to overcome barriers related to consciousness, which are high among patients with MV. Mobilization practices should be optimized according to situations and barriers, irrespective of COVID-19 infection, the kind of disease, and its severity.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many studies have been focused on the physical health of the elderly (1)(2)(3). With the increase of age, the deterioration of physical function will lead to multiple diseases and physical problems, such as non-communicable diseases (4).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 13 studies showed that the implementation of a ventilator bundle significantly reduced mortality (odds ratio 0.90, 95%CI 0.84–0.97) [ 48 ]. Another systematic review of 45 randomized clinical trials involving 5493 participants showed that daily sedation interruption significantly reduced mechanical ventilation duration, ICU stay, sedation duration, tracheostomy and VAP risks [ 49 ]. In another improvement collaborative, the implementation of the ABCDEF bundle was associated with lower likelihood of hospital death within 7 days [ 17 ].…”
Section: Discussionmentioning
confidence: 99%